Predoperativni odvzemi krvi za avtotransfuzijo na Zavodu RS za transfuzijsko medicino - Gregorc, Cvetka (Obzornik zdravstvene nege, 2006)
Autotransfusion is the safest way of blood transfusion. Donor and recipient isthe same person so there is no possibility of alloimunization or transmission of infectious diseases. Preoperative autologous donation is the most frequent way of autologous blood collection. The article presents preoperative autologous donation in Europe, the Unified States of America and in Slovenia. The description research method was used. The date about structure of autologous blood donors are taken from computer data basis DATEK and from 2315 sheets of blood-donors on Blood transfusion centre in Ljubljana in period 2001 to 2005. The madn users of preoperative autologous transfusion are the Orthopaedic clinic in Ljubljana and Orthopaedic hospital in Valdotra, where the procedure was used most often in the frames of hip replacement surgery. Most patients are from 50-80 years old. More than half of them are women (58%). Before the surgery the majority of patients donate two unit of blood (900 ml). After donation the rate of Hb decreases on average for 7g/l. The use of iron suplemments to increse red blood cell mass are prescribed to all patients after blood donation. In the five years period, approximately half of the hospital departments the Clinical Centre in Ljubljana have given up programme of autotransfusion. Reasons should be investigated further. The use of autotransfusion also depends on physicians and nurses education and patients preference.
Keywords: avtotransfuzija; Blood Donors; Blood Transfusion, Autologous; Krvna transfuzija avtologna; Krvodajalci; Predoperativna oskrba; Preoperative Care; transfuzija